EDUKASI PENDAMPINGAN PENGOBATAN SERTA PENGETAHUAN PENCEGAHAN TUBERKULOSIS PADA PENDERITA TB DI PUSKESMAS MARTAPURA 1 KABUPATEN BANJAR (STIKes Mitra Keluarga, 2023)
Tuberculosis (TB) is still a big problem in Indonesia, currently Indonesia is in 2nd place with the highest TB burden in the world, even though TB ​​treatment has been carried out for decades, TB cases have not shown a decline to date. In 2021, the number of tuberculosis cases in South Kalimantan is among the 6 provinces with the lowest percentage in terms of treatment coverage, namely 26.8%. The counseling carried out is a form of community service that is integrated by the research of lecturers from the DIII Health Analyst Study Program at the Kalimantan Leading Polytechnic which involves collaboration with the Community Health Center. Martapura 1. Martapura 1 Community Health Center has the highest number of TB patients, namely 91 residents in Banjar Regency, with BTA positive at 31.66%. Counseling activities were carried out at Martapura 1 Community Health Center with a total of 10 TB patients coming. The community is very enthusiastic about this activity. It is recommended that community health centers provide ongoing education, especially regarding treatment support for tuberculosis patients to prevent non-communicable diseases.